Effects of low-dose rapamycin on lymphoid organs of mice prone and resistant to accelerated senescence - Barros, Rafael dos Santos; Queiroz, Luiz Adriano Damasceno; Assis, Josiane Betim de; Pantoja, Kamilla Costa; Bustia, Sofia Xavier; Sousa, Emanuella Sarmento Alho de; Rodrigues, Stephen Fernandes; Akamine, Eliana Hiromi; Sá-Nunes, Anderson; Martins, Joilson O. (Frontiers in Immunology, 2024)
Aging is a complex, natural, and irreversible phenomenon that subjects the body to numerous changes in the physiological process, characterized by a gradual decline in the organism’s homeostatic mechanisms, closely related to immunosenescence. Here, we evaluated the regulation of immunosenescence in lymphoid organs of senescence-accelerated prone 8 (SAM-P8) and senescence-accelerated resistant 1 (SAM-R1) mice treated with a low dose of rapamycin (RAPA). Mice were treated with a dose of 7.1 µg/kg RAPA for 2 months and had body mass and hematological parameters analyzed prior and during treatment. Cellular and humoral parameters of serum, bone marrow, thymus, and spleen samples were evaluated by ELISA, histology, and flow cytometry. Changes in body mass, hematological parameters, cell number, and in the secretion of IL-1β, IL-6, TNF-α, IL-7, and IL-15 cytokines were different between the 2 models used. In histological analyses, we observed that SAM-P8 mice showed faster thymic involution than SAM-R1 mice. Regarding the T lymphocyte subpopulations in the spleen, CD4+ and CD8+ T cell numbers were higher and lower, respectively, in SAM-P8 mice treated with RAPA, with the opposite observed in SAM-R1. Additionally, we found that the low dose of RAPA used did not trigger changes that could compromise the immune response of these mice and the administered dose may have contributed to changes in important lymphocyte populations in the adaptive immune response and the secretion of cytokines that directly collaborate with the maturation and proliferation of these cells.